2016
DOI: 10.1016/j.chb.2016.02.090
|View full text |Cite
|
Sign up to set email alerts
|

The effect of web advertising visual design on online purchase intention: An examination across gender

Abstract: With web advertising growing to be a huge industry, it is important to understand the effectiveness of web advertisement. In this study we investigate the effects of web advertising visual design (WAVD) purchasing intention within the framework of an integrated model. Nine hypotheses were developed and tested on a dataset of 316 observations collected via a questionnaire survey. The results of structural equation modeling (SEM) indicate that while web advertising visual cues influence consumers' purchasing int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
152
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(174 citation statements)
references
References 115 publications
11
152
3
8
Order By: Relevance
“…Such differences have a neurological basis, with women associating with greater levels of engagement and trust (Riedl et al, 2010), as well as Hedonic shopping activities (Huang and Yang, 2010;Kalia, 2017;Kotzé et al, 2012). Earlier research by Chen (2007) and Shaouf et al (2016) found that men prefer e-Commerce channels more than women, who show a greater preference for high street retail. However, these conclusions focus on western consumers and therefore the generalisability to the Chinese market is untested.…”
Section: The Influence Of Demographics In Fashion Retailmentioning
confidence: 99%
“…Such differences have a neurological basis, with women associating with greater levels of engagement and trust (Riedl et al, 2010), as well as Hedonic shopping activities (Huang and Yang, 2010;Kalia, 2017;Kotzé et al, 2012). Earlier research by Chen (2007) and Shaouf et al (2016) found that men prefer e-Commerce channels more than women, who show a greater preference for high street retail. However, these conclusions focus on western consumers and therefore the generalisability to the Chinese market is untested.…”
Section: The Influence Of Demographics In Fashion Retailmentioning
confidence: 99%
“…It is important for hoteliers to determine the factors that influence purchase intention at this stage of the prepurchase (Lien et al, 2015). The level of purchases will increase if positive purchase intention is more powerful than the weak intention (Shaouf et al, 2016). Based on the results of a survey conducted by Nielsen Global Survey of e-commerce, it is found that travel services are the most widely planned by consumers to purchase online.…”
Section: Introductionmentioning
confidence: 99%
“…(2) In addition, it has been reported that the advertisement's design influences consumers' purchasing intentions through advertising and brand attitudes. (3) Therefore, for more effective marketing, it is important to consider the advertisement's design, such as the placement and color of the scheme.…”
Section: Introductionmentioning
confidence: 99%